Big hover or big brother? Public attitudes about drone usage in domestic policing activities. Issue 4 (October 2017) - Sakiyama, Mari; Miethe, Terance D; Lieberman, Joel D; Heen, Miliaikeala S J; Tuttle, Olivia
Abstract Unmanned aerial systems (that is, UAS or drones) have been increasingly proposed and used by federal and state law enforcement agencies as an evolving technology for general surveillance, crime detection and criminal investigations. However, the use of UAS technology, in general, and within the particular context of domestic policing activities raises serious concerns about personal privacy and the greater intrusion of new forms of 'big brother' surveillance in people's daily lives. On the basis of a national survey, the current study provides empirical evidence on public attitudes about UAS usage in various policing activities. Socio-demographic differences in the public support for drone usage in this context are also examined. Our general findings of context-specific variability in public support for UAS usage in policing operations are discussed in terms of their implications for developing public policy.